Answer:
C2H6O(aq) + 3O2(g) → 2CO2(g) + 3H2O(l)
Explanation:
Step 1: data given
The reactants are:
ethanol = C2H6O(aq)
oxygen gas = O2(g)
The products are:
gaseous carbon dioxide = CO2(g)
liquid water = H2O(l)
Step 2: The unbalanced equation
C2H6O(aq) + O2(g) → CO2(g) + H2O(l)
Step 3: Balancing the equation
C2H6O(aq) + O2(g) → CO2(g) + H2O(l)
On the left side we have 2 time C (in C2H6O), on the right side we have 1x C (in CO2). To balance the amount of C on both sides, we have to multiply CO2 on the right side by 2.
C2H6O(aq) + O2(g) → 2CO2(g) + H2O(l)
On the left side we have 6x H (in C2H6O), on the right side we have 2x H(in H2O). To balance the amount of H on both sides, we have to multiply H2O on the right side by 3.
C2H6O(aq) + O2(g) → 2CO2(g) + 3H2O(l)
On the right side we have 7x O (4x O in 2CO2 and 3x O in 3H2O), on the left side we have 3x O (1x in C2H6O and 2x in O2). To balance the amount of O on both sides, we have to multiply O2 on the left side by 3. Now the equation is balanced.
C2H6O(aq) + 3O2(g) → 2CO2(g) + 3H2O(l)